Nalmefene is effective at reducing alcohol seeking, treating alcohol‐cocaine interactions and reducing alcohol‐induced histone deacetylases gene expression in blood. (18th July 2016) - Calleja‐Conde, Javier; Echeverry‐Alzate, Victor; Giné, Elena; Bühler, Kora‐Mareen; Nadal, Roser; Maldonado, Rafael; Rodríguez de Fonseca, Fernando; Gual, Antoni; López‐Moreno, Jose Antonio
Abstract: Background and Purpose: The opioid antagonist nalmefene (selincro®) was approved for alcohol‐related disorders by the European Medicines Agency in 2013. However, there have been no studies regarding the effectiveness of nalmefene when alcohol is used in combination with cocaine. Experimental Approach: Using operant alcohol self‐administration in Wistar rats and qRT‐PCR, we evaluated (i) the dose–response curve for s.c. and p.o. nalmefene; (ii) the effects of nalmefene with increasing concentrations of alcohol; (iii) the efficacy of nalmefene on cocaine‐potentiated alcohol responding; and (iv) the gene expression profiles of histone deacetylases ( Hdac 1–11) in peripheral blood in vivo and in the prefrontal cortex, heart, liver and kidney post mortem . Key Results: S.c. (0.01, 0.05, 0.1 mg·kg −1 ) and p.o. (10, 20, 40 mg·kg −1 ) nalmefene dose‐dependently reduced alcohol‐reinforced responding by up to 50.3%. This effect of nalmefene was not dependent on alcohol concentration (10, 15, 20%). Cocaine potentiated alcohol responding by approximately 40% and nalmefene (0.05 mg·kg −1 ) reversed this effect of cocaine. Alcohol increased Hdac gene expression in blood and nalmefene prevented the increases in Hdac s 3, 8, 5, 7, 9, 6 and 10. In the other tissues, alcohol and nalmefene either did not alter the gene expression of Hdac s, as in the prefrontal cortex, or a tissue‐ Hdac ‐specific effect was observed. Conclusions and Implications: Nalmefene might be effective as a treatment for alcohol‐dependent patients who also use cocaine. Also, the expression of Hdacs in peripheral blood might be useful as a biomarker of alcohol use and drug response.